Macroeconomic priorities and crash states - Kevin D. Salyer (University of California, Department of Economics, 2005)
This paper reproduces Lucas's analysis of the costs of business cycles in an economy with a low probability, crash state in consumption growth. For reasonable parameter values, it is shown that the presence of a crash state dramatically increases the costs ofconsumption volatility. Specifically, for relative risk aversion around 5, households in the US economy would, in aggregate, pay over 60 billion (approximately 3% of consumption in 2001) to eliminate consumption uncertainty. The conclusion is that stabilization policy is important not for its effects on second moments but inreducing kurtosis by lowering both the probability and severity of a crash state.
Keywords: E10; E32; E60; 330; Makroökonomik; Konjunktur; Soziale Kosten; Theorie